A statistical and syntactical approach to datawarehouse design quality. (18th January 2008) - Pighin, Maurizio; Ieronutti, Lucio
Data warehousing allows analysts and managers to interactively study transactional data for deriving information suitable to support decision processes. However, the effectiveness of such tools strongly depends on taken design choices and quality of initial data. The selection of proper measures and dimensions is not a trivial task, especially in the case of large transactional databases. We propose an approach based on statistical and syntactical aspects that can be effectively used for: guiding the attributes selection during the datawarehouse design; evaluating the quality of taken design choices. We tested on three commercial databases the effectiveness of our proposal.